Research on Loaded Transmission Error of Internal Short Tooth Spur Gears - Yin Xunmin; Jia Haitao; Zhang Xijin (Jixie chuandong)
Loaded transmission error is an important parameter in evaluating the meshing performance of gears. The smaller the fluctuant amplitude of the loaded transmission error is, the better the meshing performance is. In view of the insufficient research on loaded transmission error of internal spur gears, software Romax is used to establish models of internal short tooth spur gear pairs in this research. The influence of tooth profile and gear helix modification parameters on fluctuant amplitude of loaded transmission error is studied, and some influence laws of the modification parameter on the fluctuant amplitude are obtained. A modification optimization method for internal short tooth spur gear pairs is investigated using the particle swarm algorithm. The research results lay a foundation for improving the meshing performance of internal short tooth spur gears.